2018
DOI: 10.1055/s-0038-1660781
|View full text |Cite
|
Sign up to set email alerts
|

Person-Centered, Skilled Services Using a Montessori Approach for Persons with Dementia

Abstract: The current mandate for person-centered care throughout the health care system, and especially in the nursing home industry, requires that speech-language pathologists ensure that the services they provide to elders with dementia are skilled, person centered, and relevant to positive overall health outcomes. Guidelines developed by the Association Montessori International Advisory Board for Montessori for Aging and Dementia are one avenue toward such skilled and person-centered services. The purpose of this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For example, SLPs can facilitate decision-making in PWD through caregiver training in supported communication strategies about valued daily activities, food, and clothing choices 2 . SLPs can also make changes to the environment to maximize engagement in valued activities by providing visual aids or compensatory strategies to ensure that the individual is able to participate 8 . Specifically, the Montessori approach, which aligns with PCC principles, provides evidence-based guidelines on how to select and adapt activities and structure the living environment to maximize participation 8 .…”
Section: The Role Of Slps In Person-centered Dementia Carementioning
confidence: 99%
See 1 more Smart Citation
“…For example, SLPs can facilitate decision-making in PWD through caregiver training in supported communication strategies about valued daily activities, food, and clothing choices 2 . SLPs can also make changes to the environment to maximize engagement in valued activities by providing visual aids or compensatory strategies to ensure that the individual is able to participate 8 . Specifically, the Montessori approach, which aligns with PCC principles, provides evidence-based guidelines on how to select and adapt activities and structure the living environment to maximize participation 8 .…”
Section: The Role Of Slps In Person-centered Dementia Carementioning
confidence: 99%
“…2 SLPs can also make changes to the environment to maximize engagement in valued activities by providing visual aids or compensatory strategies to ensure that the individual is able to participate. 8 Specifically, the Montessori approach, which aligns with PCC principles, provides evidence-based guidelines on how to select and adapt activities and structure the living environment to maximize participation. 8 Bourgeois et al 9 reported positive outcomes of the Montessori approach in dementia care, including individuals showing increased independence, identifying with meaningful roles, and contributing to the community, which resulted in higher levels of self-esteem.…”
mentioning
confidence: 99%
“…To support care team members in developing a meaningful and safe environment for the PWD, we suggest incorporating principles of Montessori for Dementia and Aging, such as freedom, structure and choice, nature, atmosphere, and specialized materials (Douglas et al, 2018;Montessori for Dementia and Ageing, n.d.). This environment should incorporate multimodal cues (e.g., auditory, visual, olfactory, and tactile) and include items that are meaningful to the PWD, such as personal photographs, old furniture, or personal awards.…”
Section: Counseling+ Activities For Pwd During Residential Long-term Carementioning
confidence: 99%
“…The type of activity and level of facilitation is based on the interests, abilities and needs of the individual and should be failure free. In a care home setting this may be, for example, a laundry sorting activity (Douglas et al., 2018).…”
mentioning
confidence: 99%